Two new species of Psechrus Thorell, 1878 (Araneae: Psechridae) from India - Sudhin, Puthoor Pattammal; Mali, Shouvik; Sen, Souvik (Zootaxa, 2026)
Two new species of Psechrus Thorell, 1878, P. ntu sp. nov. (♀) and P. phenshunyu sp. nov. (♀) are described from the Indian state of Nagaland. Additionally, P. himalayanus Simon, 1906 is recorded for the first time from northeastern India. The record of P. himalayanus is based on a male specimen found cohabiting a web of P. phenshunyu sp. nov., suggesting that heterospecific association may occur among the members of this genus. Detailed morphological descriptions and illustrations of the copulatory organs of the new species are provided along with the natural history observations and distribution map of the Psechrus species currently known from India.